2017
DOI: 10.1002/2327-6924.12526
|View full text |Cite
|
Sign up to set email alerts
|

After-hours/on-call experience during primary care nurse practitioner education utilizing standard scenarios and simulated patients

Abstract: Background and purpose Few nurse practitioner (NP) programs include an after‐hours/on‐call component in their clinical preparation of NP students. This role is expected in many primary and specialty care practices, and is one that students feel unprepared to competently navigate. Methods Utilizing simulated callers as patients or parents, NP students participated in a simulated after‐hours/on‐call experience that included receiving the call, managing the patient, and submitting documentation of the encounter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…This study loosely replicated the on-call study completed by Kelly et al (2017). The students in this study were adult gerontology acute care students rather than primary care; therefore, the scenarios reflect the types of calls commonly made by the nursing staff caring for hospitalized patients.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This study loosely replicated the on-call study completed by Kelly et al (2017). The students in this study were adult gerontology acute care students rather than primary care; therefore, the scenarios reflect the types of calls commonly made by the nursing staff caring for hospitalized patients.…”
Section: Discussionmentioning
confidence: 75%
“…The Kelly et al (2017) study's perception surveys served as the foundation for the development of the surveys in this study. Questions and responses were altered to reflect the roles and responsibilities of the adult gerontology ACNP provider where they deviated from those of a primary care provider.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 A similar study suggested that complex decision making by NPs in primary health care is safe and effective within the limitations of a telephone consultation. 22 NPs in many of these settings were also able to contribute to the nursing team as educators and agents of quality improvement. 8,23 NPs are known to support other nurses through a process of collaborative decision making within a nursing team model of care that differentiates them from physicians.…”
Section: Introductionmentioning
confidence: 99%